Gambaran Epidemiologi dan Evaluasi Sistem Surveilans Pneumonia di Puskesmas Cilembang Kota Tasikmalaya Tahun 2024 - Nenih Nurhasanah; Aprilla Andini; Anisa Febriani; Sephia Zandra (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Pneumonia is an acute respiratory infection that remains a major public health issue in Indonesia, particularly among infants and children. West Java is among the provinces with a high number of cases, and in 2024, Tasikmalaya City reported 2,178 cases, with Cilembang Public Health Center (Puskesmas Cilembang) recording the highest number. This study aims to evaluate the P2 ISPA (pneumonia) surveillance system at UPTD Puskesmas Cilembang. A descriptive-evaluative method was used, involving interviews, document reviews, and observations with surveillance and P2 ISPA program officers at the Tasikmalaya City Health Office and Puskesmas Cilembang. The findings indicate that the pneumonia surveillance implementation at Puskesmas Cilembang is fairly adequate, although improvements are needed to better align with current guidelines and government regulations.